Implementasi Pendidikan Diniyah Formal Wustha di Pondok Pesantren Abinnur Al-Islami Desa Mompang Jae - Muhammad Basri; Ali Jusri Pohan; Khairurrijal (PT. Willy Print Art, 2024)
The aim of this research is to describe the implementation of formal diniyah education from the curriculum aspect, from the aspect of educators and teaching staff, and from the assessment aspect at the Abinnnur Al-Islami Islamic boarding school. This type of research is qualitative research. Data collection techniques are observation, interviews and documentation. Data validity techniques, source triangulation, technical triangulation and member checks. Data analysis techniques use reduction, data display, conclusion drawing/verification. The results of this research are that the implementation of the curriculum is running well in accordance with applicable regulations as per the 2020 Minister of Religion regulations. The learning resources implemented emphasize the majority of religious learning at 75% and general learning at 25%. The aspect of educators and educational staff at the Abinnur Al-Islami Islamic boarding school is from undergraduate graduates and Islamic boarding school graduates in accordance with the 2020 Minister of Religion regulations in articles 39, 40, 41. The assessment aspect is that educators carry out daily assessments which are carried out in various ways from attendance, giving assignments can in the form of writing and memorization, educators even directly observe students' activities, to assess all competency achievements, mid-semester and end-of-semester assessments are carried out. So the implementation of Formal Early Education (PDF) at the Abinnur Al-Islami Islamic Boarding School is in accordance with the 2020 Minister of Religion Regulations both in terms of the learning resources used, the criteria for educators and education staff as well as the assessment process carried out.